Effect of postpartum glucose tolerance results on subsequent weight retention in women with recent gestational diabetes: A retrospective cohort study. (May 2019) - Purno, Nabila H.; Thorpe, Kevin; Mukerji, Geetha; Ray, Joel; Lowe, Julia; Feig, Denice S.; Lipscombe, Lorraine L.
Abstract: Aims: Glucose tolerance normalizes postpartum in most women with gestational diabetes (GDM), which may provide false reassurance and decrease weight-reducing behaviours. We evaluated whether awareness of normal postpartum glucose tolerance was associated with higher weight retention than being unaware of glucose tolerance. Methods: This cohort study of women with GDM collected survey data during pregnancy and in the first and second postpartum year. We compared women who reported normal glucose tolerance ('aware, normal') in the first year to those reporting no testing or unsure of results ('unaware'). The primary outcome was self-reported weight in the second year compared between groups using multivariable linear regression. Results: Among 319 women, 110 (34.5%) were 'aware, normal'; 183 (57.4%) were 'unaware'; and 26 (8.2%) were 'aware, abnormal'. After adjusting for baseline weight and covariates, women with normal results had a mean 3.66 kg higher weight (CI 1.08–6.24 kg, p = 0.0056) by the second year than those unaware of results. Conclusions: Women with GDM with normal postpartum glucose tolerance had significantly higher weight by the second year than those unaware of their results. Normal glucose tolerance after pregnancy may be misinterpreted as resolution of diabetes risk and decrease risk-reducing behaviours.